Imprisonment pains, reentry strains, and perceived likelihood of reoffending. Issue 1 (2nd January 2021) - Cook, Amanda; Haynes, Stacy Hoskins
ABSTRACT: Research has shown that imprisonment has a criminogenic effect, but few studies have examined why this relationship exists. Drawing on Agnew's General Strain Theory (GST) and survey data from a sample of men and women incarcerated in a large Southern prison, the current study examined the role of both imprisonment pains and reentry strains on perceived likelihood of reoffending. It also examined differences between first-time and repeat prisoners. Results from the overall sample showed that reentry strains (i.e., low community capital and inability to adjust to life in the community) mattered more than imprisonment pains. The results were similar for repeat prisoners, but both imprisonment pains (i.e., fear for one's safety while in prison) and reentry strains (i.e., low community capital) mattered for first-time prisoners.